Genetic Evidence Supports a Major Role for Akt1 in VSMCs During Atherogenesis. Issue 11 (22nd May 2015) - Rotllan, Noemi; Wanschel, Amarylis C.; Fernández-Hernando, Ana; Salerno, Alessandro G.; Offermanns, Stefan; Sessa, William C.; Fernández-Hernando, Carlos
<x xml:space="preserve">Abstract</x> Rationale: Coronary artery disease, the direct result of atherosclerosis, is the most common cause of death in Western societies. Vascular smooth muscle cell (VSMC) apoptosis occurs during the progression of atherosclerosis and in advanced lesions and promotes plaque necrosis, a common feature of high-risk/vulnerable atherosclerotic plaques. Akt1, a serine/threonine protein kinase, regulates several key endothelial cell and VSMC functions including cell growth, migration, survival, and vascular tone. Although global deficiency of Akt1 results in impaired angiogenesis and massive atherosclerosis, the specific contribution of VSMC Akt1 remains poorly characterized. Objective: To investigate the contribution of VSMC Akt1 during atherogenesis and in established atherosclerotic plaques. Methods and Results: We generated 2 mouse models in which Akt1 expression can be suppressed specifically in VSCMs before (Apoe−/−Akt1fl/flSm22αCRE) and after (Apoe−/−Akt1fl/flSM-MHC-CreERT2E) the formation of atherosclerotic plaques. This approach allows us to interrogate the role of Akt1 during the initial and late steps of atherogenesis. The absence of Akt1 in VSMCs during the progression of atherosclerosis results in larger atherosclerotic plaques characterized by bigger necrotic core areas, enhanced VSMC apoptosis, and reduced fibrous cap and collagen content. In contrast, VSMC Akt1 inhibition in established atherosclerotic plaques does not influence lesion size but markedly reduces the relative fibrous cap area in plaques and increases VSMC apoptosis. Conclusions: Akt1 expression in VSMCs influences early and late stages of atherosclerosis. The absence of Akt1 in VSMCs induces features of plaque vulnerability including fibrous cap thinning and extensive necrotic core areas. These observations suggest that interventions enhancing Akt1 expression specifically in VSMCs may lessen plaque progression.